Satisfaction of mothers with midwifery care in - Ahmadi, Z; Azimi, H (Advances in Nursing & Midwifery, 2010)
Background and aim Midwifery care plays an important role in provision and promotion of maternal health. Therefore, its evaluation is necessary and one of the ways for that is to measure satisfaction of mothers with the care given to them. This descriptive study was conducted to identify the level of satisfaction of mothers with midwifery care in labor and delivery rooms at hospitals of Zanjan city. Materials and methods 100 women were randomly selected from obstetrical units after delivery. A questionnaire in 2 parts, namely, demographics and maternal satisfaction, was used for data collection. Its validity and reliability were achieved by content and Cronbach’s α methods respectively. Data were analyzed by SPSS 14. Different statistical tests including chi-square, Pearson coefficient of correlation and t-student were used for data analysis. Findings Mean age of the subjects was 25.80±4.58. Total satisfaction was %74.6 in which %35, %53 and %12 had high, moderate and low levels of satisfaction respectively. No significant correlation was found between the level of satisfaction and such demographic characteristics as age, level of education, occupation, parity and sex of newborns. Conclusion Satisfaction of mothers with midwifery care in labor and delivery rooms was moderate to high. High satisfaction of mothers in this study may indicate an appropriate and desirable care provided by midwives. Thus, employing midwifery work force is essential for maternal health promotion. Keywords: Satisfaction, Midwifery care, Delivery. *Corresponding Author: Lecturer, Islamic Azad University, Zanjan Branch. Zanjan, Iran E-mail: Ahamdi.Zahra4@gmail.com